Akad Tijarah Lainnya pada Asuransi Syariah : Studi Kasus Prudential Syariah dan Allianz Life Syariah Indonesia - Maryam Fany; Sindi Setiawat; Muhammad Zahran Hidayatul Urfa; Joni Joni; Raihani Fauziah (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
Islamic insurance (takaful) is a financial instrument that functions not only as risk protection but also as an investment tool based on sharia principles. So far, the most commonly applied tijarah contracts in Islamic insurance are limited to wakalah bil ujrah and mudharabah. In fact, the development of modern society’s needs requires the diversification of contracts so that the offered products become more varied and competitive. This study aims to analyze the potential optimization of other tijarah contracts, such as musyarakah, murabahah, ijarah, and istishna’, in the development of Islamic insurance products. The research method used is library research with a descriptive qualitative approach, which involves reviewing literature, journals, DSN-MUI fatwas, and related regulations. The findings indicate that the application of other tijarah contracts has the potential to enrich Islamic insurance product variations, enhance transparency in fund management, and strengthen the competitiveness of Islamic insurance compared to conventional insurance. Furthermore, the diversification of contracts can provide solutions to the limited and monotonous business models of Islamic insurance. However, several challenges arise, including the absence of specific regulations governing these contracts, limited public understanding, and technical complexities in implementation. This study recommends the active role of regulators, especially DSN-MUI and OJK, in formulating clearer regulations and encouraging Islamic insurance companies to innovate by applying diverse sharia-based contracts. Thus, the optimization of other tijarah contracts will not only strengthen the existence of Islamic insurance in Indonesia but also fulfill society’s demand for financial products that are halal, innovative, and competitive.